The prevention of postoperative complications in gynecological patients - S A Levakov; N A Sheshukova; E I Borovkova; O V Bolshakova (IP Berlin A.V., 2015)
The study allowed to compare the clinical efficacy of the drug and antibiotic Terzhinan gynecological patients operated on for tubal peritoneal factor infertility. In women receiving traditional intraoperative antibiotic prophylaxis, the antimycotic treatment followed 2 weeks; after surgery the violation of the qualitative and quantitative composition of the microflora of the vagina was observed, which further required additional therapy. In patients who used Terzhinan, dysbiotic violations in the vagina were observed only in 2 women was a decrease in the number of representatives of the indigenous microflora. Thus, the local use of antibacterial drugs in the perioperative period can be considered as an alternative to the system or the single use of antibiotics, which allows to recommend their use in order to reduce the incidence of inflammatory and infectious diseases of the vagina in gynecological patients before and after surgery.